Coronal leakage of provisional restorative materials used in endodontics with and without intracanal medication after exposure to human saliva - P Udayakumar; Mamta Kaushik; Neha Prashar; Shikha Arya (Wolters Kluwer Medknow Publications, 2016)
Aim: To determine the coronal leakage of various provisional restorations with and without intracanal medication over time after being exposed to human saliva. Materials and Methods: This study investigated Coltosol F, Cavit, Ketac Molar, and IRM as provisional restorative material. Calcium hydroxide and chlorhexidine were used as an intracanal medicament. Ninety-eight single rooted teeth were randomly selected and then mounted in an apparatus that isolated the crown portion of the tooth. Provisional restorative materials were placed in the access cavity following manufacturer guidelines after placement of intracanal medicament. Human saliva and brain heart infusion broth in 3:1 ratio were applied to the samples, incubated at 37°C, and results were tabulated over the course of 4 weeks by the appearance of turbidity in the lower part of the apparatus. Statistical Analysis: The data were statistically analyzed using proportional Z-test. The level of significance was set at 0.05. Results: Coltosol F and Cavit could significantly prevent the bacterial leakage up to a period of 7 days with a P value of 0.01 and 0.005, respectively. Bacterial recontamination was relatively less in the samples treated with intracanal medicaments up to 14 days. After 14 days, however, all materials leaked in over half of the samples. Conclusion: No provisional restorative material can be considered superior in providing a reliable seal after 14 days. Inter-appointments schedule should not extend beyond 2 weeks and after endodontic therapy final restoration should be completed within 1 week.